TREATMENT OF DYSLIPIDEMIA IN TYPE 2 DIABETES MELLITUS PATIENTS AT THE DIABETES CLINIC, HOSPITAL SULTAN HAJI AHMAD SHAH: A CLINICAL AUDIT - An, Teo Jin; Hui, Lau Chia; Suhaimi, Nur Aziera binti; Hamzah, Nurul Athirah binti; Shudim, Saiful Shahrizal; Keong, See Chee (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Dyslipidemia is a major risk factor for cardiovascular disease in patients with Type 2 Diabetes (T2D) and requires aggressive management. The aim of this clinical audit is to assess the appropriateness of dyslipidemia treatment in T2D patients attending the diabetes clinic at Hospital Sultan Haji Ahmad Shah, Temerloh, Pahang. METHODOLOGY All T2D patients attending the diabetes clinic from June to July 2024 were included in this clinical audit. Electronic medical records were reviewed for demographic data, comorbidities, lipid profiles, cardiovascular disease risk assessments, and statin prescription patterns. RESULT A total of 102 patients were included, with a mean age of 53.2 years, 55.9% being female, and 59.8% having a diabetes duration of more than 10 years. The majority of patients had high to very high cardiovascular risk. Among the patients, 37.3% had chronic kidney disease and 32.4% had ischemic heart disease. The LDL-C control at the latest follow-up was suboptimal, with a mean LDL-C of 2.71 mmol/L. Additionally, 33.3% of patients were not initiated on the appropriate statin intensity, and 12% did not receive any lipid-lowering therapy. 20% of patients were on high doses of atorvastatin (60–80 mg), with limited use of combination therapy. Despite recognizing the patients’ cardiovascular risk, there was clinical inertia in intensifying treatment. CONCLUSION This clinical audit highlights weaknesses in adherence to clinical guidelines and clinical inertia in dyslipidemia treatment. There is a greater need for continuous education and a stronger emphasis on achieving treatment goals in the management of T2D patients. Additionally, a reassessment of the budget for the availability of combination therapy options is necessary.